Gerakan Lansia Sehat dan Mandiri Melalui Healthy Home Service - Cahya Tribagus Hidayat; Sofia Rhosma Dewi; Hardian Oktavianto (Journal of Community Development, 2025)
The aging population phenomenon that will occur in 2030-2050 will cause a shift in the elderly population with a dependency ratio that continues to increase. When someone reaches old age, they will face the peak of the human life cycle. The increasing number of older people will also cause various problems such as technical, medical, psychological, mental, and socio-economic problems. The various problems that arise if not managed properly will have an impact on the elderly, namely physical changes in the elderly, causing them to feel unable to do various activities as well as when they were young. This causes the elderly to become then demotivated and withdraw from the social environment. This condition requires special attention. These problems can reduce life expectancy in the elderly. The form of community empowerment for the elderly is the Healthy and Independent Elderly Movement (GLSM) through Healthy Home Service as a form of UKBM (Community-Based Health Efforts). Healthy Home Service provides services in the form of health education services, elderly cadre training, modality therapy, and telenursing services, as well as SIM-RS (Hospital Management Information System), which facilitates online-based health services and also accommodates a database that records data on the number of elderly diseases. The results of the activities obtained were an increase in the knowledge and attitudes of the elderly regarding achieving optimal quality of life by 96.66%. The knowledge and understanding of the elderly increased, in addition to an increase in the productivity of elderly companion cadres, along with the structure and main tasks for elderly companion cadres by 100%. Elderly cadres have understood their roles and duties.